Experimental study on long-term compressive strength of concrete with manufactured sand. (1st April 2016) - Ding, Xinxin; Li, Changyong; Xu, Yangyang; Li, Fenglan; Zhao, Shunbo
Highlights: Long-term compressive strength of concrete with manufactured sand (MSC) was examined. Explain effects of stone powder on workability and compressive strength development. Forecast model of long-term compressive strength of MSC are proposed. Abstract: In this paper, experimental studies on compressive strength development of concrete with manufactured sand were carried out. Influences of stone powder content on long-term compressive strength of concrete with different water-to-cement ratios were analyzed. Tests results showed that when content of stone powder was less than 13%, it basically had positive correlation with the long-term compressive strength of MSC. Based on tests data, forecast model of long-term compressive strength of MSC considering curing age, water-to-cement ratio and cement's compressive strength and density are proposed.